Prevalence and Predictors of Anger and Hostility in Secondary School Teachers of Public and Private Sector - none, Safia Umer; Saddiqui, Jawaid Ahmed; Memona; Sadiq, Riffat (Journal of Pakistan Psychiatric Society, 2020)
OBJECTIVE: To examine the prevalence and predictors of anger and hostility in secondary school teachers of public and private sectorSTUDY DESIGN: Correlational Study with Prediction Research DesignPLACE AND DURATION OF STUDY: The study was carried out in Karachi from April 2017 to February 2019.SUBJECTS AND METHODS: Total two hundred secondary schools teachers including one hundred (n =100) from public sector and one hundred (n =100) from private sector participated in the present study.  Data was obtained through personal information sheet, subscales of Anger and Hostility Job Satisfaction Survey and Satisfaction With Life Scale. Data was statistically analyzed by descriptive statistics and multiple regression analysis with SPSS, Version, 22.0.RESULTS: Among secondary school teachers, about 66% from public sector and 73% from private sector reported significant anger. Approximately, 47% teachers of public sector and 54% from private schools reported significant hostility. Job satisfaction and life satisfaction significantly predicted anger among teachers of both public and private sector. Job satisfaction significantly predicted hostility in teachers of public sector but not in teachers of private sector. However, life satisfaction did not emerge as significant predictor of hostility among both groups of participants. CONCLUSION: Secondary school teachers of both public and private sector experienced anger and hostility. Job Satisfaction and life satisfaction constitute significant portion of anger among all. Teachers of public sector harbor hostility owing to job satisfaction only. However, life satisfaction did not seem to play a significant role in determining hostility.